Assessment of genetic variability and character association for yield contributing traits in mungbean (Vigna radiata L.): Genetic Variability & Yield Traits of Mungbean - Sharmin, S; Shompa, BN; Parveen , S; Siddikee, MA (Bangladesh Journal of Agriculture, 2026)
The study was conducted to evaluate the genetic variability and correlation between several yield contributing features in mungbean (Vigna radiata L.). Fourteen mungbean varieties from different Institutes, were evaluated with nine quantitative traits during the Kharif I season from March to June, 2020 at the Sher-e-Bangla Agricultural University's research farm. The analysis of variance showed significant variation among all the varieties in all the traits studied. The phenotypic variances were greater than the genotypic variances. The Phenotypic coefficient of variance and genotypic coefficient of variance were higher for the no. of branches /plant (19.671; 18.309) followed by weight. of 1000 seed (g) (25.339; 25.254) and yield/plant (g) (31.296; 31.049) respectively. High heritability coupled with high genetic advance as a percent of mean was observed for plant height (cm) (96.073; 21.421), followed by no. of leaves/plant (95.977 ; 31.950), no. of branches /plant (86.636 ; 35.107), no. of pods/plant (99.335; 55.623), pods length/plant (cm) (98.389 ; 29.455), no. of seeds/pod (92.371 ;33.375), weight of 1000 seed (g) (99.331; 51.848) and yield/plant (g) (98.427 ; 63.456), respectively which indicated the effect of additive genes effect. In the correlation co-efficient analysis yield/plant had significant positive relation at both the genotypic and phenotypic level with the number of leaves/plants followed by number of branches/plants, number of pods/plants, number of pods cluster/plant, pods length/plant (cm), number of seeds/pod and weight. of 1000 seed (g) which indicates this character can be considered for future improvement program of mungbean. Path analysis revealed that number of seeds/pod (0.689), number of leaves/plant (0.338), number of branches/plant (0.196), number of pods/plant (0.435) and weight of 1000 seed (g) (0.016) showed positive direct effect on yield/plant. These results suggest that the direct selection of these characters will facilitate the chance of simultaneous improvement of other traits in mungbean. Evaluating the performance among the studied varieties, BINA mung5 and BINA mung8 considered the elite variety. Bangladesh J. Agri. 2025, 50(2): 147-157